Greenhouse Salt Tunnel as Innovation to Create Salt Production in the South Coast Malang Regency, Indonesia - Amin, Abd. Aziz; Yanuar, Adi Tiya; Kurniaty, Rika; Hakim, Lukman; Ardian, Gatot; Amenan, M.; Kurniawan, Andi (Postgraduate School of Universitas Brawijaya, 2023)
Seawater is one of the potential resources in Indonesia. One of the commodities that can be produced from seawater is salt. Salt production in Indonesia is done mainly by evaporating seawater. However, weather problems are one of the obstacles to salt production. Alternative innovation to overcome weather problems in salt production is the Greenhouse Salt Tunnel (GST). The application of this innovation allows salt production to be carried out throughout the year. Most salt businesses in East Java are located on the north coast of East Java, while there is no salt production on the South Coast of East Java. One of the locations in East Java that can be used for salt production is the South Coast of Malang Regency. However, studies analyzing the need for innovation to create salt production in the South Coast of Malang Regency have never been reported. This study aimed to analyze the application of GST innovation to create salt production in the South Coast of Malang Regency. The methodologies were analyzing the suitability index of salt production sites, soil elevation analysis, wind direction and speed, and construction requirements for GST. The results show that Gajahrejo Village is very suitable for salt production. The salt production can be conducted using 12 GST constructions on a 2000 m2 area. According to the results of this study, salt production in the south coast area of Malang Regency can be created using the application of GST innovation. Keywords: aquatic resources, greenhouse salt tunnel, solar salts; south coast of Java, technology innovation